Self-perception and perceived parental perception in adolescent girls with anorexia nervosa - Sokolov, Mariana; Levy-Schiff, Rachel; Enoch-Levy, Adi; Stein, Daniel (Frontiers in Psychology, 2024)
Negative self-perception is associated with poor outcome in adults with anorexia nervosa (AN). Our aim was to assess the association of self-perception of female adolescents with AN, and of the way in which these adolescents perceive the attitudes of their parents to them on the severity and short-term outcome of their illness. For this purpose, we assessed 30 adolescent females hospitalized with AN and 30 control females. Self-perception and perceived parental attitudes were assessed using the Structural Analysis of Social Behavior (SASB), according to which, self-perception is formed via close relations with significant others in early life. Patients with AN responded to the SASB and to questionnaires assessing eating disorder (ED) symptomatology and emotional distress at admission and discharge. Controls were similarly assessed once. We found that patients with AN showed a more negative self-perception than controls. Negative self-perception was associated with negative perception of the mothers' attitudes toward the girls. There was no between-group difference in the perceived perception of the fathers' attitude to the girl. Self-perception and perceived parental attitudes were associated with the severity of ED symptoms and emotional distress. Last, an improvement was found in self-perception and perceived maternal attitudes toward the girl from admission to discharge, alongside a decrease in the severity of ED symptoms and emotional distress. Self-perception at admission was associated with ED-pathology and emotional distress at discharge. These findings suggest that self-perception and perceived parental attitudes toward the adolescent with AN may be associated with the severity of the illness and its short-term outcome.